A perfect moral storm the ethical tragedy of climate change - Gardiner, Stephen Mark. (New York ; Oxford : Oxford University Press, 2011)
Climate change is arguably the great problem confronting humanity, but we have done little to head off this looming catastrophe. In this work, Gardiner illuminates our dangerous inaction by placing the environmental crisis in an entirely new light, considering it as an ethical failure.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Environmental ethics; Global warming -- Moral and ethical aspects; Climatic changes -- Moral and ethical aspects; Environmental responsibility